Selenium WebDriver recipes in C# - Zhan, Zhimin (Expert's voice in Web development., 2015)
Selenium WebDriver Recipes in C#, Second Edition is a quick practical problem-solving guide to automated testing web applications with Selenium WebDriver in C#. This book contains hundreds of solutions to real-world problems, with clear explanations and ready-to-run Selenium test scripts that you can use in your own projects. What You'll Learn How to locate web elements and test functions for hyperlinks, buttons, TestFields and TextAreas, Radio Buttons, CheckBox, and more How to use Selenium WebDriver for select lists, navigation, assertions, frames, file upload and pop-up dialogs How to debug test scripts and test data How to manage and deal with browser profiles and capabilities How to manage tests for advanced User Interactions and Experiences (UX) How to work with and manage tests and testing using the Selenium Remote Control Server and more.